A Facile Synthesis of Blue Luminescent [7]Helicenocarbazoles Based on Gold‐Catalyzed Rearrangement‐Iodonium Migration and Suzuki–Miyaura Benzannulation Reactions. Issue 30 (4th May 2018) - Alcaide, Benito; Almendros, Pedro; Aragoncillo, Cristina; Busto, Eduardo; López‐Calixto, Carmen G.; Liras, Marta; de la Peña O'Shea, Víctor A.; García‐Sánchez, Alba; Stone, Hannah V.
Abstract: New azahelicenes having interesting photophysical properties have been prepared in a four‐step sequence. These [7]helicenocarbazoles are efficient blue luminophores, demonstrating the utility of gold catalysis in the preparation of advanced materials. Abstract : Shining blue : A four‐step sequence from commercial precursors, has allowed for the preparation of new azahelical 6‐5‐6‐6‐6‐5‐6 derivatives, which are efficient blue luminophores.